MiR-302 Regulates Glycolysis to Control Cell-Cycle during Neural Tube Closure - Keuls, Rachel A. (Int J Mol Sci, 2020)
Neural tube closure is a critical early step in central nervous system development that requires precise control of metabolism to ensure proper cellular proliferation and differentiation. Dysregulation of glucose metabolism during pregnancy has been associated with neural tube closure defects (NTDs) in humans suggesting that the developing neuroepithelium is particularly sensitive to metabolic changes. However, it remains unclear how metabolic pathways are regulated during neurulation. Here, we used single-cell mRNA-sequencing to analyze expression of genes involved in metabolism of carbon, fats, vitamins, and antioxidants during neurulation in mice and identify a coupling of glycolysis and cellular proliferation to ensure proper neural tube closure. Using loss of miR-302 as a genetic model of cranial NTD, we identify misregulated metabolic pathways and find a significant upregulation of glycolysis genes in embryos with NTD. These findings were validated using mass spectrometry-based metabolite profiling, which identified increased glycolytic and decreased lipid metabolites, consistent with a rewiring of central carbon traffic following loss of miR-302. Predicted miR-302 targets Pfkp, Pfkfb3, and Hk1 are significantly upregulated upon NTD resulting in increased glycolytic flux, a shortened cell cycle, and increased proliferation. Our findings establish a critical role for miR-302 in coordinating the metabolic landscape of neural tube closure.